Effectiveness of a culturally competent care intervention in reducing disparities in Hispanic live donor kidney transplantation: A hybrid trial. Issue 2 (17th October 2021) - Gordon, Elisa J.; Uriarte, Jefferson J.; Lee, Jungwha; Kang, Raymong; Shumate, Michelle; Ruiz, Richard; Mathur, Amit K.; Ladner, Daniela P.; Caicedo, Juan Carlos
Abstract : Hispanic patients receive disproportionately fewer living donor kidney transplants (LDKTs) than non‐Hispanic Whites (NHWs). The Northwestern Medicine Hispanic Kidney Transplant Program (HKTP), designed to increase Hispanic LDKTs, was evaluated as a nonrandomized, implementation‐effectiveness hybrid trial of patients initiating transplant evaluation at two intervention and two similar control sites. Using a mixed method, observational design, we evaluated the fidelity of the HKTP implementation at the two intervention sites. We tested the impact of the HKTP intervention by evaluating the likelihood of receiving LDKT comparing pre‐intervention (January 2011–December 2016) and postintervention (January 2017–March 2020), across ethnicity and centers. The HKTP study included 2063 recipients. Intervention Site A exhibited greater implementation fidelity than intervention Site B. For Hispanic recipients at Site A, the likelihood of receiving LDKTs was significantly higher at postintervention compared with pre‐intervention (odds ratio [OR] = 3.17 95% confidence interval [1.04, 9.63]), but not at the paired control Site C (OR = 1.02 [0.61, 1.71]). For Hispanic recipients at Site B, the likelihood of receiving an LDKT did not differ between pre‐ and postintervention (OR = 0.88 [0.40, 1.94]). The LDKT rate was significantly lower for Hispanics at paired control Site D (OR = 0.45 [0.28, 0.90]). The intervention significantly improved LDKT rates for Hispanic patients at the intervention site that implemented the intervention with greater fidelity. Registration: ClinicalTrials.gov registered (retrospectively) on September 7, 2017 (NCT03276390). Abstract : A non‐randomized, implementation‐effectiveness hybrid trial shows that high fidelity implementation of an intervention, the Northwestern Medicine Hispanic Kidney Transplant Program, increases Hispanic living donor kidney transplantation, highlighting the Program's potential to reduce Hispanic disparities.